Realidades De La Recreación Y La Actividad Física En Los Grupos De Adulto Mayor De La Cuidad De Armenia (2014)
The present research investigates the realities of recreation in Older Adults belonging to the elderly groups of the city of Armenia Quindío, these realities can be understood as the concepts that the older adults have about recreation and physical activity. And the concepts of authors who contribute in this research, this project was developed under a comprehensive approach to research, type of study quasi-ethnographic, used as data collection instruments observation and in-depth interview. The findings showed three macro categories. Recreation as a means to health and prevention of disease. This finding was very prominent since in the great majority of the A M they take the assistance to these groups as a means for the prevention of illnesses and maintenance at the physical level and of the health. From the social environment of the older adult for recreational physical activities it was evidenced that the MA besides performing these activities as health maintenance see it as a way to integrate people and create bonds of friendship and solidarity very strong where they come to be considered a family . Technical Implements for functional AM Another fundamental finding was the lack of instruments in this finding is manifested the lack of support and sponsorship of some public and private entities towards the AM groups of the city of Armenia since the majority are very few Implements that they possess for the practice of some physical exercises and in others they are improvised implements